The Drosophila homologue of Rootletin is required for mechanosensory function and ciliary rootlet formation in chordotonal sensory neurons - Styczynska-Soczka, Katarzyna (Cilia, 2015)
BACKGROUND: In vertebrates, rootletin is the major structural component of the ciliary rootlet and is also part of the tether linking the centrioles of the centrosome. Various functions have been ascribed to the rootlet, including maintenance of ciliary integrity through anchoring and facilitation of transport to the cilium or at the base of the cilium. In Drosophila, Rootletin function has not been explored. RESULTS: In the Drosophila embryo, Rootletin is expressed exclusively in cell lineages of type I sensory neurons, the only somatic cells bearing a cilium. Expression is strongest in mechanosensory chordotonal neurons. Knock-down of Rootletin results in loss of ciliary rootlet in these neurons and severe disruption of their sensory function. However, the sensory cilium appears largely normal in structure and in localisation of proteins suggesting no strong defect in ciliogenesis. No evidence was found for a defect in cell division. CONCLUSIONS: The role of Rootletin as a component of the ciliary rootlet is conserved in Drosophila. In contrast, lack of a general role in cell division is consistent with lack of centriole tethering during the centrosome cycle in Drosophila. Although our evidence is consistent with an anchoring role for the rootlet, severe loss of mechanosensory function of chordotonal (Ch) neurons upon Rootletin knock-down may suggest a direct role for the rootlet in the mechanotransduction mechanism itself.